2019
DOI: 10.1001/jamanetworkopen.2019.18324
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Mortality Rates Associated With Invasive Group B Streptococcus Infections Among Patients in the US Veterans Health Administration

Abstract: IMPORTANCE The incidence of invasive infections caused by group B Streptococcus (GBS) continues to increase in the United States. Although diabetes is a key risk factor for invasive GBS, the influence of long-term glycemic control is not well characterized; other risk factors and mortality rates associated with specific types of invasive GBS infections are unknown. OBJECTIVE To investigate risk factors and mortality rates associated with specific invasive GBS infectious syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…Our results are similar to those reported in the literature as global in-hospital mortality for non-pregnant adults is estimated to range from 3 to 23.7% worldwide [1,2,16]. Other factors previously associated with mortality are cancer, septic shock, peritonitis, endocarditis, and meningitis [8,23].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those reported in the literature as global in-hospital mortality for non-pregnant adults is estimated to range from 3 to 23.7% worldwide [1,2,16]. Other factors previously associated with mortality are cancer, septic shock, peritonitis, endocarditis, and meningitis [8,23].…”
Section: Discussionsupporting
confidence: 90%
“…There is a plethora of studies which attempted to characterize the adults most susceptible to invasive GBS infection. While obesity and diabetes are most common underlying conditions associated with substantially increased risk of infection and mortality [10][11][12] , the role of NAFLD with GBS invasive disease outcomes has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Kremers et al pointed out that the incidence of diabetes associated with osteomyelitis increased in the US with a higher prevalence in males than in females [ 62 ]. A more recent study demonstrated that the incidence of osteomyelitis more than doubled between 2008 and 2017 [ 63 ]. These results may explain the increased mortality rate with time in the present study.…”
Section: Discussionmentioning
confidence: 99%